2020
DOI: 10.1097/iop.0000000000001521
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Acquired Nasolacrimal Duct Obstruction as a Specific Complication of Treatment With Radioactive Iodine (Morphological Study)

Abstract: Purpose: To conduct a morphological study of structural changes in the nasolacrimal duct in secondary acquired nasolacrimal duct obstruction (SALDO) as a result of treatment with radioiodine. Methods: Twenty patients (20 cases) were involved: 10 cases with secondary acquired nasolacrimal duct obstruction at Hasner’s valve level due to the treatment with radioiodine (group 1) and 10 cases with primary acquired nasolacrimal duct obstruction (group 2). Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…Previous studies on the comparative pathomorphological analysis of changes in Hasner's valve in PANDO and SALDO due to radioactive iodine therapy have shown that in the latter case speci c changes characterized as radiation damage to Hasner's valve develop [2]. It was found that in SALDO desquamation of the nasolacrimal duct epithelium and damage to the mucous glands are observed which is accompanied by moderate brosis, while in PANDO brosis is relatively more pronounced and is apparently a consequence of a long-running chronic in ammatory process.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies on the comparative pathomorphological analysis of changes in Hasner's valve in PANDO and SALDO due to radioactive iodine therapy have shown that in the latter case speci c changes characterized as radiation damage to Hasner's valve develop [2]. It was found that in SALDO desquamation of the nasolacrimal duct epithelium and damage to the mucous glands are observed which is accompanied by moderate brosis, while in PANDO brosis is relatively more pronounced and is apparently a consequence of a long-running chronic in ammatory process.…”
Section: Discussionmentioning
confidence: 96%
“…Experience has shown that such obstruction develops most often in the distal segments of the nasolacrimal duct and is characterized by some pathomorphological features that distinguish primary and secondary acquired lacrimal drainage system obstruction [2]. A comparative study of changes in the lacrimal drainage system at various anatomical levels in patients with PANDO and SALDO due to radioactive iodine therapy has not yet been conducted, although the results of such a study would provide information concerning the pathogenesis of these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…7 Fedorov et al reported the morphological changes associated with nasolacrimal duct obstruction as a complication from I-131, and observed desquamation of columnar epithelium, ulceration of nasolacrimal duct wall, and necrobiotic mucous glands. 13 Additionally, they compared the histologic changes observed to primary acquired nasolacrimal duct obstruction in which they report a mixed inflammatory reaction suggestive of chronicity. This highlights the molecular difference in the pathological process of developing nasolacrimal duct obstruction secondary to I-131.…”
Section: Discussionmentioning
confidence: 99%
“…The tear fluid is a blood ultrafiltrate, where some components can be in higher concentrations than in blood. Once the drugs gain adequate access to the tear ducts, their toxicity on the mucous membranes results in undesirable effects 11,12 …”
Section: Introductionmentioning
confidence: 99%